A assistência à infância desvalida no Espírito Santo: o orfanato Cristo Rei (1957-1990) - Tourinho, Márcia Selvátice (2009)
This study is part of the problem of assistance to children and adolescents in Brazil abandoned. The aim is to draw a picture of the actions developed by the state and society to assist these children, observing and showing particularly the example of Christ the King Orphanage, located in Vitoria, the city of Vitoria, Espirito Santo State, especially from 1957 to 1990, which begins when Sister Marcelina of St. Louis took the institution, extending to the year of the promulgation of the Statute for Children and Adolescents. From sources such as literature on the subject, documents Orphanage Lord and stories of the characters involved in the matter, seek to contextualize the importance of the role of Sister Marcelina in the institution and its compliance with directives coming from the public policies for child care and Teen abandoned in the state of Espirito Santo.